Pengelolaan Sampah Berbasis Zero Waste Melalui Sistem Perkebunan Minimalis di RT. 19 Kelurahan Bukit Pinang Kota Samarinda - Rinda, Rizky Sulvika Puspa; Nizaora, Ditha; Kurnyawaty, Noorma (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2025)
Abstract Public awareness of waste management has increased over the past decade. The government has carried out numerous of waste management outreach from the national level to the sub-district level, which is the separation of organic and non-organic waste. Bukit Pinang Village is one of the sub-districts located in Samarinda Ulu District, Samarinda City, East Kalimantan. RT 19 is one of the RTs in Bukit Pinang Village where several residents have awareness about the separation of organic and non-organic household waste. However, the knowledge about organic waste management is still inadequately implemented. This was seen from the fact that many residents still throw it away in final disposal sites and some residents even burn their household waste, which of course disrupts air quality. Through this Community Science Program, counselling was provided on the management of organic household waste using a zero waste-based system that has broad and long-term benefits such as the plantation sector in a simple (minimalist) concept to housewives in RT 19. Participants were equipped with knowledge about improving the processing of household waste into more useful products, such as minimalist gardens and compost, so that local residents can manage their own waste while also having minimalist production gardens.